Rencana Zoning Kawasan Wisata Air di Hutan Kota pada Lahan Bekas Tambang Batubara PT Bukit Asam, (Tbk) Tanjung Enim, Kabupaten Muara Enim - Kiki Andriani; Nurini Nurini (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
Mine activity can give adverse environmental impacts significantly. Land conversion as mine land demanding reclamation activities on demanding reclamation activities. Reclamation is an activity that is required for mining entrepreneurs. PT Bukit Asam us one of the largest mining company in South Sumatera, district Muara Enim committed to undertake reclamation activities which will be implemented in urban forest development H.Kalamudin Djinab, SH, MH on post land mining. The land area that will be built into the urban forest of 50 hectares consisting some zoning.The design method is carried out from field survey activities, and observation to obtain the required data as well as in compiling secondary and primary data. The analyzes in preparing zoning plan of urban forest consist of space requirement analysis, activity analysis, user characteristic analysis, space organization analysis, site analysis and zoning area. So that zoning of urban forest area will be developed into several different functions in each area